ANALISIS PILIHAN WAJIB PAJAK ANTARA PAJAK PENGHASILAN DAN PAJAK ATAS KONSUMSI : EFEK SIKLUS HIDUP BERPERILAKU (BEHAVIORAL LIFE CYCLE) (Studi Empirik: Wajib Pajak di DKI Jakarta) - Ghozali, Imam; Amaludin, Mochamad (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2004)
The objectives of this study is to analize whether changing in public's preference for income taxes as opposed to expenditure taxes might had something to do with changing demography. The Study was aimed to be The Study of Behavior Life Cycle Hyphothesis (BLCH) to prove the theory's claim that pubic preference tor income taxes as opposed to expenditure taxes might rely on individual position on his/her life cycle. His/her position also determined his/her self controling ability (in delaying consumption to the future) and his/her intention (in mentally segregating income into distict accounts which carry different marginal propensities to consume).By doing Zimmerman's et.al. (1995) study as a replication with some adjustment to meet Indonesia demographic conditions (Jakarta population as a sample) and tax system which we/IÂknown in Indonesian tax regulation system, this study had pick sample of Jakarta tax payer individuals (with some judgement to meet Indonesian demographic representation). The questionaires were distributed during June Â August 2003 to two Big Five accounting firm (Ernst and Young, Hanadi Sarwoko, Sandjaya and Price Water House Coopers (PWCs, Hadisusanto and co.) and Jakarta Regional Tax Offices (iv, V, VI and VII). There were 40,27% response rate or 149 out of 370 questionaires distributed (2 questionaires were dropped). The study was using Structural Equation Modelling (SEM) as its statistical examination instrument, and using AMOS 2003 statistics application. This study have documented some findings which imply BLCH individual might view increased income taxes as a penalty on their own productive performance but either view increased consumption taxes as the reflection of unequity issue. In aging population, instead of supporting 1995 Zimmerman et. al. study which had documented agreement with increased consumption taxes, the result of this study not suggest the shifting public preference from income taxation to consumption taxation intact this study found the population reacted against both increased income taxes and increased consumption taxes which may be related to changing demographics.